Heat Exchangers - Advanced Features and Applications 2017
DOI: 10.5772/65896
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Heat Transfer on Geometrically Enhanced Horizontal Tube: A Review

Abstract: In this chapter, an attempt has been made to present the recent state of knowledge of free-convection condensation heat transfer on geometrically enhanced tubes. This survey is divided into three sections. The first section concentrates on research on condensate flooding or retention. The second and the third sections cover the experimental and the theoretical work on geometrically enhanced tubes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Interesting results were obtained as condensing tubes were found unaffected by the variation of mass-flow rate. An extensive literature review on condensate retention on enhanced tubes has also been reported by Ali [22].…”
Section: Film-wise Condensationmentioning
confidence: 82%
“…Interesting results were obtained as condensing tubes were found unaffected by the variation of mass-flow rate. An extensive literature review on condensate retention on enhanced tubes has also been reported by Ali [22].…”
Section: Film-wise Condensationmentioning
confidence: 82%
“…In the recent years, different manufacturing techniques are used to enhance the heat transfer effects by maximizing the surface area resulting change in the fin profiles. A 3D rectangular cross section "pin -fin" geometry can be constructed since the criterion to judge the condensation heat transfer effects only an integral-fin tube is not enough [19,27,[100][101][102][103]. Tubes comprising such tubes are called "pin-fin tubes" and are clarified by six dimensions in particular such as: pin-root diameter, longitudinal pin spacing and thickness, circumferential pin spacing and thickness, and pin height [100].…”
Section: Pin-fin Tubesmentioning
confidence: 99%
“…Recently Ali and Briggs [20] published an analytical model which predict most of the experimental data on pin-fin tubes to within ±15%. Ali also summarized the previous work on enhanced tubes successfully [22].…”
Section: Introductionmentioning
confidence: 97%